Хірургічне лікування нейроендокринних пухлин підшлункової залози - Павловський, М. П.; Коломійцев, В. І.; Бойко, Н. І.; Лукавецький, О. В.; Гавриш, Я. І.; Наконечний, Б. О.; Лерчук, О. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
The own 25-years experience of surgical treatment of 38 patients with pancreatic neuroendocrine tumors (30 patients had insulinoma, 5 — gastrinoma, 3 — carcinoid) was presented. The type of operation and choice of access depended on the kind of tumor, localization and size. In cases of tumors of body and/or tale of the pancreas the operation of choice was distal (or caudal) pancreatectomy; in cases of pancreatic head tumors the pancreatduodenectomy, duodenpreseved caputpancreatectomy or enucleation of tumor masses were performed. 5 patients were operated laparoscopicaly: 3 adenoma enucleation and 2 distal pancreatectomies. In case of malignancy the metastases resection and/or lymphadenectomy were added. Postoperative period was complicated with acute pancreatitis in 3 patients, pancreatic fistula — 4 patients. One patient (2.6%) died because of pancreonecrosis.